PROSWIFT Bill and the 2020 Space Weather Operations and Research Infrastructure Workshop From the National Academies of Sciences, Engineering, and Medicine - Noé Lugaz (Space Weather)
Abstract The Space Weather Research and Forecasting Act (PROSWIFT) passed the U.S. Senate in July 2020 and the House of Representative on 16 September; it directs NOAA to capture remote images of coronal mass ejections (CMEs) with the Space Weather Follow‐On at L1 (SWFO‐L1) mission. A workshop organized by an ad hoc committee of the National Academies of Sciences, Engineering, and Medicine had its second part held in 9–11 September 2020 to discuss future space weather operations and research infrastructure in the medium term. Discussions included low‐Earth orbit (LEO) constellations, measurements of geomagnetically induced currents (GICs) and future cislunar and interplanetary measurements.